Ethnophysics Flipbook Based on Acehnese Islamic Values to Improve Students’ Physics Literacy - Saminan, Saminan; Hanik, Ummi; Zainuddin, Zainuddin; Rasul, Muhammad Sattar; Abidin, Zainal (Yayasan Keluarga Guru Mandiri, 2026)
Acehnese have long used measuring instruments for various daily needs, but these measuring instruments have not been utilized as media in the teaching and learning in schools. This study aims to develop an Ethnophysics flipbook based on Islamic values from Acehnese culture to improve students’ physics literacy. The flipbook is designed by integrating basic physics concepts, such as the measurement of mass, volume, and time, with local cultural practices, for example, the use of kai, are, naleh, and mayam, as well as the application of time in economic and religious activities, including zakat. This integration is expected not only to improve understanding of physics concepts but also to instill religious values and strengthen local wisdom. This study uses the Research and Development (RD) method with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects were high school students in Banda Aceh, and the instruments included expert validation sheets, student response questionnaires, and physics literacy tests. The results of expert validation showed very high feasibility. The limited trial obtained a positive response from 95% of students and a significant increase in physics literacy with an N-Gain of 0.78 (high category). In conclusion, the Islamic-values-based Ethnophysics flipbook effectively increased physics literacy that was contextual, religious, and relevant to local culture, while strengthening Islamic identity and preserving Acehnese culture.